The effects of chemical composition, solidification rate, and homogenization on the intermetallic particle microstructure of AA8XXX aluminum alloys for battery foil applications - Maluleka, Tshepo (Department of Mechanical Engineering, 2025)
The growing demand for high-performance lithium-ion batteries, driven by the electric vehi-cle (EV) market, necessitates the development of current collectors that offer both superior electrical conductivity and enhanced mechanical properties. AA1XXX series aluminum al- loys, commonly used in battery applications, are limited by their strength and ductility. As an alternative, AA8XXX aluminum alloys, particularly those based on the Al-Fe-Si system, show promise due to their improved strength. However, their intermetallic particle (IMP) microstructure needs to be understood for optimal performance. This research investigates the impact of chemical composition, cooling rate, and homoge- nization processes on the IMP microstructure of AA8021 and AA8079 alloys, which are poten-tial candidate alloys for this application. Using 2D and 3D analytical approaches supported by analytical tools including light microscopy (LM), scanning electron microscopy (SEM), scanning transmission electron microscopy (STEM) and X-ray diffraction (XRD). The study identified three primary morphologies: plate-shaped, feathery/skeletal, and needle-shaped, corresponding to Al3Fe, AlmFe, and Al6Fe phases. The results reveal that higher Fe content in AA8021 leads to a higher volume fraction of finer IMPs, while higher Si content in AA8079 enhances the stability of Al3Fe and reduces the presence of AlmFe. Further- more, cooling rate significantly influences IMP morphology and phase stability, with higher cooling rates favoring the formation of finer, metastable phases at the surface. Homogeniza-tion treatments induce phase transformations from metastable Al6Fe and AlmFe to the stable Al3Fe phase, improving the uniformity and distribution of IMPs.